Numerical solution of structural mechanics boundary problems with the use of wavelet-based boundary element method - Kaytukov, T B; Mozgaleva, M L; Akimov, P A (IOP conference series. Materials Science and Engineering, 2018)
The distinctive paper is devoted to theoretical foundations of boundary problems' numerical mechanics solution with the use of wavelet-based boundary element method (BEM). Particularly the simplest boundary problem for Laplace operator is under consideration. Initial continual formulation of boundary problems, simple-layer potential basics and double-layer potential (including their properties), numerical solutions of Dirichlet and Neumann problems (so-called "boundary" systems of linear equations) are presented.